2015
DOI: 10.1002/jbmr.2709
|View full text |Cite
|
Sign up to set email alerts
|

The Roles and Mechanisms of Actions of Vitamin C in Bone: New Developments

Abstract: Vitamin C is an important antioxidant and cofactor which is involved in the regulation of development, function and maintenance of several cell types in the body. Deficiencies in vitamin C can lead to conditions such as scurvy, which, among other ailments, causes gingivia, bone pain and impaired wound healing. This review examines the functional importance of vitamin C as it relates to the development and maintenance of bone tissues. Analysis of several epidemiological studies and genetic mouse models regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(153 citation statements)
references
References 107 publications
3
141
0
2
Order By: Relevance
“…It is important that the patient begins receiving nutritional support in the intensive care unit (ICU) during the initial postoperative course . Vitamin C has long been known to be critically important in the collagen formation of surgical wound healing; however, recent investigations have shown it plays a role in bone healing as well . Selenium is utilised by fibroblasts during the proliferative phase of wound healing and has become an invaluable wound‐healing supplement that is gaining use in postoperative nutritional regimens .…”
Section: Techniquementioning
confidence: 99%
“…It is important that the patient begins receiving nutritional support in the intensive care unit (ICU) during the initial postoperative course . Vitamin C has long been known to be critically important in the collagen formation of surgical wound healing; however, recent investigations have shown it plays a role in bone healing as well . Selenium is utilised by fibroblasts during the proliferative phase of wound healing and has become an invaluable wound‐healing supplement that is gaining use in postoperative nutritional regimens .…”
Section: Techniquementioning
confidence: 99%
“…It was reported that the antioxidative substance vitamin E could prevent SAON due to its antioxidant property [22]. Vitamin C (VC) is a more portent antioxidant than vitamin E that VC also has benefit effect on bone development and maintenance by promoting genes producing bone matrix in osteoblasts [23]. VC supplementation may therefore attenuate SAON and promote the repair of SAON through its antioxidative effect and bone-anabolic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Scurvy is a clinical diagnosis with features that may include bleeding and swollen gums, loosening of teeth, bone abnormalities, arthralgia, delayed wound healing, anaemia and classic skin findings of perifollicular hyperkeratosis, petechiae and purpura. Fever can occur in the later stages of the disease …”
Section: Discussionmentioning
confidence: 99%